Pengaruh Pengawasan Melekat Terhadap Disiplin Kerja Pegawai Pada Kantor Camat Lambu - Herlin Herlin; Muhammad Yusuf (ARBITRASE: Journal of Economics and Accounting, 2020)
Supervision is carried out for the process in determining performance measures and taking actions that can support the achievement of expected results in accordance with the specified performance. discipline of civil servants is the ability of civil servants to obey obligations and avoid prohibitions specified in legislation regulations and / or kedisan regulations which if not adhered to or violated are subject to disciplinary punishment. This study aims to determine the effect of inherent supervision of the Employee Work Discipline in Lambu District Office. The type of research that is used is associative, the research is located at the Bima District Head Office. The population in this study were 48 people who were all employees of Lambu Sub-District office. consisting of 33 Civil Servants (PNS), and 15 Regional Contract Workers (TK2D). The number of samples used in this study amounted to 33 people who are civil servants (PNS). The sampling technique used is purposive sampling. The research instrument used a questionnaire with a Likert scale. The type of data used is quantitative data from primary data sources. Data collection techniques are observation, documentation, questionnaire and literature study. Data analysis includes validity test, reliability test, simple linear regression analysis, simple correlation analysis, determination test and t test. The results of data analysis showed that there was no influence between the inherent supervision of Employee Work Discipline in the Lambu Sub-District Office. With a tcount of 0.544, smaller than t table 1.696 (0.544 <1.696) and a Sig> 0.05 (0.590> 0.05)